2020
DOI: 10.1111/bcp.14196
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of topical β‐receptor blocker in treating superficial infantile haemangiomas: A meta‐analysis including 20 studies

Abstract: Aims To evaluate the effectiveness and safety of topical β‐receptor blocker in treating superficial infantile haemangiomas (SIH) and compare the effectiveness and safety of topical β‐receptor blocker against other therapies. Methods A search of the literature using PubMed, Embase, Cochrane Review database, China National Knowledge Infrastructure and Wanfang were performed to identify the studies that estimated the effectiveness and safety of topical β‐receptor blocker in treating SIH, the fixed‐effect or rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 27 publications
(57 reference statements)
2
34
0
Order By: Relevance
“…Several reports have described similar outcomes using topical beta-blockers for the treatment of superficial periocular IH and two large recent meta-analyses, involving 1235 and 2098 children, concluded that topical beta-blockers may replace oral propranolol as first-line treatment for superficial IH due to its comparable effectiveness and reduced adverse effects [8,9].…”
Section: Discussionmentioning
confidence: 90%
“…Several reports have described similar outcomes using topical beta-blockers for the treatment of superficial periocular IH and two large recent meta-analyses, involving 1235 and 2098 children, concluded that topical beta-blockers may replace oral propranolol as first-line treatment for superficial IH due to its comparable effectiveness and reduced adverse effects [8,9].…”
Section: Discussionmentioning
confidence: 90%
“…However, since 0.5% topical timolol appears to be the most widely used formulation, 2 , 7 , 8 a meta‐analysis conducted by Ng et al in 2016, focused more extensively on the therapeutic protocols rather than on the concentrations, showing that encouraging results are indeed possible with different 0.5% topical timolol administration protocols (1 drop BID, 2 drops BID, 3 drops TID/QID, 3 drops TID), as Global Assessment Score greater than 3 (which indicates an acceptable clinical improvement) was registered in 47% up to 88% of cases. 9 …”
Section: Beta‐blockers In Infantile Hemangioma Treatmentmentioning
confidence: 99%
“… 6 To date, there is an appreciable number of studies that support the efficacy and safety of TTM in term infants with IHs. 70 76 A meta-analysis in 2020 showed that TTM is likely non-inferior to oral propranolol (OR 0.955, 95% CI 0.700–1.302, p =0.769) in treating superficial IHs. In addition, it was superior to topical imiquimod (OR 2.561, 95% CI 1.182–5.550, p =0.017) and conservative management (OR 18.458, 95% CI 5.660–60.191, p <0.001).…”
Section: Reviewmentioning
confidence: 99%
“…Some examples of adverse reactions include desquamation, nocturnal crying, erythema and diarrhoea, all of which occurred in around 1% of cases. 76 According to Drolet et al, one drop of 0.5% TTM twice daily has the potential of reaching a plasma concentration known to have systemic beta-blocking activity in adults, especially with increasing IH thickness. In thick IHs, doses exceeding two drops of 0.5% TTM per day are not recommended and may not have the safety advantage over oral beta-blockers.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation